The Effect of Different Water Types Techniques on the Development of the Kalanchoe daigremontiana Plant - Atmaca, Emel (International journal of Horticulture, Agriculture and Food science, 2022)
Ornamental plant cultivation requires authentic notions and design skills. Kalanchoe daigremontiana, which is a noteworthy ornamental plant in this sector, which generally operates as a family business, has recently started to take place in both pots and terrariums. This plant, which saves a lot of water due to being a CAM (Crassulaceae Acid Metabolism) plant, continues its lineage with the baby leaves it forms. In this study, the effects of water, which undertakes one of the key tasks in plant development, on certain yield and growth parameters of Kalanchoe daigremontiana through its application on pure-sterile-fountain-mineral-mix varieties was investigated. In this study, in which vermicompost, which is not used much in the ornamental plant sector, and peat, which is frequently used, are applied together (1:2.5 ratio), the highest growth parameter values were obtained from plants grown in pots irrigated with distilled water. Among these values, the difference between plant height (18.00 cm), internode distance (3.77 cm), stem dry weight (0.09 g), baby leaf number (18.33 pieces/leaf) and chlorophyll (47.30) values were found statistically significant (P<0.01 and P<0.05). Nevertheless, the highest leaf number (11.33 pieces), leaf fresh and dry weight (2.91 g-0.08 g), stem fresh weight (0.86 g), leaf projection diameter (6.20 cm) and stem diameter (2.67 mm) were obtained from plants in pots treated with distilled water, however, the difference between the values was not statistically significant (P<0.01 or P<0.05). The highest values of some macronutrient and micronutrient element values of the plant were obtained from plants irrigated with pure water, yet, no nutrient deficiency was found in any plant. This can be attributed to the easier decomposition and breakdown of nutrients due to the fact that pure water dissolves the nutrients in peat and vermicompost. Indeed, the fact that the lowest growth and yield parameters are obtained in pots irrigated with mineral water and that the leaves do not form offspring, confirms this.